Maintenance Immunosuppressive Prescribing Patterns in Kidney Transplant Recipients at an Indonesian Tertiary Referral Hospital: A Retrospective Cross-Sectional Study - Dimo Pratama; Aqmarina Tamimi; Yulia Wardhani (HM Publisher, 2026)
Kidney transplantation is the optimal kidney replacement therapy for end-stage kidney disease, but graft survival depends on lifelong maintenance immunosuppression. Indonesian data on how these medicines are actually prescribed remain scarce. Retrospective cross-sectional drug-utilisation study of 53 maintenance immunosuppressant prescriptions dispensed to kidney transplant recipients at a tertiary referral hospital in Yogyakarta, Indonesia, between 2017 and 2024. Proportions were estimated with Wilson 95% confidence intervals (CI); within-class preference with exact binomial tests; associations with Fisher exact tests; prescribing concentration with diversity indices and bootstrap CIs; and frequencies were benchmarked against published French, Korean and Indonesian reference proportions using Holm-adjusted exact binomial tests, reported as absolute differences and prevalence ratios. Reporting followed STROBE. Recipients were mostly aged 18–49 years (73.6%) and male (64.2%). Tacrolimus was the only calcineurin inhibitor prescribed (100.0%; 95% CI 93.2–100.0), and mycophenolic acid the only antiproliferative agent. Methylprednisolone was the preferred corticosteroid (69.8%; 56.5–80.5; p = 0.002) and enteric-coated mycophenolate sodium the preferred formulation (77.4%; 64.5–86.5; p < 0.001). The modal regimen was tacrolimus plus methylprednisolone plus mycophenolate sodium (56.6%; 43.3–69.0). Tacrolimus and mycophenolic acid use exceeded a French national cohort (+8.7 and +9.5 percentage points; Holm-adjusted p = 0.040 and 0.034), whereas corticosteroid maintenance did not differ significantly (96.2% versus 88.1%; p = 0.086). Prescribing was highly concentrated (Herfindahl–Hirschman Index 3,799). In conclusion, maintenance prescribing was exceptionlessly tacrolimus- and mycophenolate-based, exceeding even high-volume European practice, and reproduced an independent Indonesian series almost exactly. Corticosteroid maintenance was near-universal, identifying corticosteroid minimisation and therapeutic drug monitoring capacity as priority targets.